Differences between US and German adults in native-born and migrants’ participation in volunteering as a dimension of civic engagement - Jovita Ross-Gordon; Anke Grotlüschen; M Cecil Smith; Thomas J. Smith; Amy D. Rose; Jill Zarestky; Marion Fleige (Adult Education Research Conference, 2020)
We examine civic engagement among immigrants and native-born adults in the United States (U.S.) and Germany, operationalized in this study as voluntary work or volunteerism. Data for the analyses are drawn from the PIAAC. Germany and the U.S. were selected from the countries participating in PIAAC initial data collection in 2012 as two large OECD countries with different histories of immigration and responses to migrants. In Germany, native-born individuals showed greater volunteerism than immigrants (β = 0.119, p < .001) while in the U.S., no significant difference was apparent by immigration status (β = 0.031, p = .133). These results are discussed in the paper relative to existing research literature and implications for adult education are suggested.
Keywords: Civic engagement; PIAAC; volunteerism